Determinants of the capital structure of TSL sector enterprises = Determinanty struktury kapitału przedsiębiorstw branży TSL (Transport, Spedycja, Logistyka) - Jędrzejczak-Gas, Janina (Zielona Góra: Faculty of Economics and Management Press)
The capital structure has been of interest for researchers in the field of financial theory for over 60 years. However, literature surveys show that relatively few studies on the structure of capital and the factors shaping it can be applied to the TSL industry. The TSL (Transport, Spedition, Logistics) sector belongs to industries with a high development potential, both in the world and Poland. In order to meet the need for the diagnosis of the TSL industry in Poland, the research was undertaken to identify and examine the strength and direction of the impact of selected factors on the capital structure of enterprises in the TFL sector in Poland.
Keywords: struktura kapitału; determinanty struktury kapitału; analiza korelacji; analiza regresji; capital structure; determinants of the capital structure; correlation analysis; regression analysis